Satisfaction and Loyalty of Consumers of Dried Mackerel (Scomberomorus commersoni) In Bengkulu City - Lestari Pakpahan; Indra Cahyadinata; Irnad Irnad (AGRITROPICA : Journal of Agricultural Sciences, 2023)
Dried mackerel fish is a type of processed mackerel fish. Even though mackerel is in dry form, many people consume it. To analyze the level of consumer satisfaction and consumer loyalty and analyze the factors that influence the level of satisfaction and loyalty of dried mackerel in the city of Bengkulu. CSI (Customer Satisfaction Index) analysis tool to analyze satisfaction levels, Loyalty Pyramid to analyze Loyalty levels and Structural Equation Modeling (SEM) to analyze the influence between variables. The results of the CSI calculation are 79.59%. Consumer loyalty for dried mackerel in Bengkulu City, with the highest score, lies in the Liking the Product category, with a value of 143%. These results indicate the level of consumer satisfaction for dried mackerel in Bengkulu City is included in the satisfaction criteria with CSI values ​​between 66% -80.99%. Loyalty levels produce an inverted pyramid shape. In the simultaneous test, the direct effect of the product quality, price and place variables significantly affect satisfaction. Still, the service quality variable does not affect satisfaction. In the simultaneous test, the direct effect of product and service quality variables significantly affects customer loyalty. In contrast, the price and place variables do not significantly affect customer loyalty. The results of the analysis of the indirect effect showed that the service quality variable has no significant effect on loyalty through satisfaction, and product quality, price and place variables have a significant effect on consumer loyalty Dried Mackerel through satisfaction. Dried Mackerel traders can maintain the taste of dried Mackerel through salting and drying processes using the PEHI LING drying concept (Practical Economical and Hygienic with an Environmental Insight).